Inequality Proof: [sum[i=1,n] a_i b_i]^2 <= [sum[i=1,n] (a_i)^2]*[sum[i=1,n] (b_i)^2]

pisrationalhahaha

New member
Joined
Aug 22, 2017
Messages
46
Inequality Proof: [sum[i=1,n] a_i b_i]^2 <= [sum[i=1,n] (a_i)^2]*[sum[i=1,n] (b_i)^2]

Can someone help me in finding a proof for this inequality please ?



. . .\(\displaystyle \displaystyle \left[\sum_{i=1}^n\, a_i\, b_i\right]^2\, \leq\, \left[\sum_{i=1}^n\, a_i^2\right]\, \times\, \left[\sum_{i=1}^n\, b_i^2\right]\)



I don't have any idea. I want a proof that I can understand because I am on my third day at university.
 

Attachments

  • ScreenCapture_2017-10-06_01.21.53.jpg
    ScreenCapture_2017-10-06_01.21.53.jpg
    11.4 KB · Views: 5
Last edited by a moderator:
Can someone help me in finding a proof for this inequality please ?



. . .\(\displaystyle \displaystyle \left[\sum_{i=1}^n\, a_i\, b_i\right]^2\, \leq\, \left[\sum_{i=1}^n\, a_i^2\right]\, \times\, \left[\sum_{i=1}^n\, b_i^2\right]\)



I don't have any idea. I want a proof that I can understand because I am on my third day at university.
Have you learned about proof by weak mathematical induction? That is what I would try first.

\(\displaystyle \displaystyle n = 1 \implies \left ( \sum_{j=1}^n \{a_jb_j\}^2 \right ) = (a_1b_1)^2 = a_1^2b_1^2.\)

\(\displaystyle \displaystyle n = 1 \implies \left ( \sum_{j=1}^n a_j^2 \right ) \left ( \sum_{j=1}^n b_j^2 \right ) = a_1^2b_1^2.\)

\(\displaystyle \displaystyle \therefore n = 1 \implies \left ( \sum_{j=1}^n \{a_jb_j\}^2 \right ) \le \left ( \sum_{j=1}^n a_j^2 \right ) \left ( \sum_{j=1}^n b_j^2 \right ).\)

Now what?
 
Last edited by a moderator:
Have you learned about proof by weak mathematical induction? That is what I would try first.

\(\displaystyle \displaystyle n = 1 \implies \left ( \sum_{j=1}^n \{a_jb_j\}^2 \right ) = (a_1b_1)^2 = a_1^2b_1^2.\)

\(\displaystyle \displaystyle n = 1 \implies \left ( \sum_{j=1}^n a_j^2 \right ) \left ( \sum_{j=1}^n b_j^2 \right ) = a_1^2b_1^2.\)

\(\displaystyle \displaystyle \therefore n = 1 \implies \left ( \sum_{j=1}^n \{a_jb_j\}^2 \right ) \le \left ( \sum_{j=1}^n a_j^2 \right ) \left ( \sum_{j=1}^n b_j^2 \right ).\)

Now what?

Ok I understand but cant we do the normal mathematical induction.
You proved the inequality for n=1 but shouldn't we after, suppose that it is true and prove it for the rank n+1 ?
 
Ok I understand but cant we do the normal mathematical induction.
You proved the inequality for n=1 but shouldn't we after, suppose that it is true and prove it for the rank n+1 ?
Yes. So try proving that if it is true for some ARBITRARY integer k \(\displaystyle \ge\) 1, it is also true for k + 1.
 
But how ?
Im stuck at this point
Any time you have a theorem that involves proving something for every integer greater than some base integer, you should consider a proof by weak mathematical induction.

There are two points about such proofs. One is that you can never be sure whether they are going to work until you try. So if you do not see any other proof, start working on the assumption that induction will work. Don't just stare at the thing; do the work, starting at n = 1.

Second, virtually all proofs by induction work similarly. After you have proved it for 1, you can assume that it is true for at least one positive integer. Let k be ANY such integer. So the theorem is true for k. Now set up the pieces for k + 1 and REDUCE them to the desired expressions in k and an expression in k + 1. When you are dealing with complex expressions, it frequently helps to replace them with simple variables to make the algebra more manageable. So here it is how it is done.

\(\displaystyle \displaystyle n = 1 \implies \left ( \sum_{j=1}^n \{a_jb_j\}^2 \right ) = (a_1b_1)^2 = a_1^2b_1^2.\)

\(\displaystyle \displaystyle n = 1 \implies \left ( \sum_{j=1}^n a_j^2 \right ) \left ( \sum_{j=1}^n b_j^2 \right ) = a_1^2b_1^2.\)

\(\displaystyle \displaystyle \therefore n = 1 \implies \left ( \sum_{j=1}^n \{a_jb_j\}^2 \right ) \le \left ( \sum_{j=1}^n a_j^2 \right ) \left ( \sum_{j=1}^n b_j^2 \right ).\)

\(\displaystyle \text {THUS, } \exists\ k \in \mathbb Z \text { such that } k \ge 1\\

\text { and } \displaystyle \left ( \sum_{j=1}^k \{a_jb_j\}^2 \right ) \le \left ( \sum_{j=1}^k a_j^2 \right ) \left ( \sum_{j=1}^k b_j^2 \right ).\)

\(\displaystyle \displaystyle \text {Let } c = \left ( \sum_{j=1}^k \{a_jb_j\}^2 \right ),\ d = \left ( \sum_{j=1}^k a_j^2 \right ),\ \text {and } e = \left ( \sum_{j=1}^k b_j^2 \right ).\)

\(\displaystyle \text {Note that } 0 \le c \le de.\)

\(\displaystyle \displaystyle \left ( \sum_{j=1}^{k+1} \{a_jb_j\}^2 \right ) = \left ( \sum_{j=1}^k \{a_jb_j\}^2 \right ) + a_{k+1}^2b_{k+1}^2 = c + a_{k+1}^2b_{k+1}^2 .\)

\(\displaystyle \displaystyle \left ( \sum_{j=1}^{k+1} a_j^2 \right ) \left ( \sum_{j=1}^{k+1} b_j^2 \right ) = \left \{ \left ( \sum_{j=1}^k a_j^2 \right ) + a_{k+1}^2 \right \}\left \{\left ( \sum_{j=1}^k b_j^2 \right ) + b_{k+1}^2 \right \} = \)

\(\displaystyle (d + a_{k+1}^2)(e + b_{k+1}^2) = de + a_{k+1}^2e + b_{k+1}^2d + a_{k+1}^2b_{k+1}^2 \implies\)

\(\displaystyle \displaystyle de + a_{k+1}^2b_{k+1}^2 = \left ( \sum_{j=1}^{k+1} a_j^2 \right ) \left ( \sum_{j=1}^{k+1} b_j^2 \right ) - (a_{k+1}^2e + b_{k+1}^2d).\)

\(\displaystyle \text {But } 0 \le (a_{k+1}^2e + b_{k+1}^2d)\ \because \text { every term is non-negative.}\)

\(\displaystyle \displaystyle \therefore de + a_{k+1}^2b_{k+1}^2 \le \left ( \sum_{j=1}^{k+1} a_j^2 \right ) \left ( \sum_{j=1}^{k+1} b_j^2 \right ).\)

\(\displaystyle \displaystyle \therefore c + a_{k+1}^2b_{k+1}^2 \le \left ( \sum_{j=1}^{k+1} a_j^2 \right ) \left ( \sum_{j=1}^{k+1} b_j^2 \right ) \ \because \ c \le de.\)

\(\displaystyle \displaystyle \text {But } \left ( \sum_{j=1}^{k+1} \{a_jb_j\}^2 \right ) = c + a_{k+1}^2b_{k+1}^2 .\)

\(\displaystyle \displaystyle \therefore \left ( \sum_{j=1}^{k+1} \{a_jb_j\}^2 \right ) \le \left ( \sum_{j=1}^{k+1} a_j^2 \right ) \left ( \sum_{j=1}^{k+1} b_j^2 \right ).\)

\(\displaystyle \displaystyle \text {THUS, by induction, for all } n \ge 1,\ \left ( \sum_{j=1}^n \{a_jb_j\}^2 \right ) \le \left ( \sum_{j=1}^n a_j^2 \right ) \left ( \sum_{j=1}^n b_j^2 \right ).\)
 
Last edited:
Any time you have a theorem that involves proving something for every integer greater than some base integer, you should consider a proof by weak mathematical induction.

There are two points about such proofs. One is that you can never be sure whether they are going to work until you try. So if you do not see any other proof, start working on the assumption that induction will work. Don't just stare at the thing; do the work, starting at n = 1.

Second, virtually all proofs by induction work similarly. After you have proved it for 1, you can assume that it is true for at least one positive integer. Let k be ANY such integer. So the theorem is true for k. Now set up the pieces for k + 1 and REDUCE them to the desired expressions in k and an expression in k + 1. When you are dealing with complex expressions, it frequently helps to replace them with simple variables to make the algebra more manageable. So here it is how it is done.

\(\displaystyle \displaystyle n = 1 \implies \left ( \sum_{j=1}^n \{a_jb_j\}^2 \right ) = (a_1b_1)^2 = a_1^2b_1^2.\)

\(\displaystyle \displaystyle n = 1 \implies \left ( \sum_{j=1}^n a_j^2 \right ) \left ( \sum_{j=1}^n b_j^2 \right ) = a_1^2b_1^2.\)

\(\displaystyle \displaystyle \therefore n = 1 \implies \left ( \sum_{j=1}^n \{a_jb_j\}^2 \right ) \le \left ( \sum_{j=1}^n a_j^2 \right ) \left ( \sum_{j=1}^n b_j^2 \right ).\)

\(\displaystyle \text {THUS, } \exists\ k \in \mathbb Z \text { such that } k \ge 1\\

\text { and } \displaystyle \left ( \sum_{j=1}^k \{a_jb_j\}^2 \right ) \le \left ( \sum_{j=1}^k a_j^2 \right ) \left ( \sum_{j=1}^k b_j^2 \right ).\)

\(\displaystyle \displaystyle \text {Let } c = \left ( \sum_{j=1}^k \{a_jb_j\}^2 \right ),\ d = \left ( \sum_{j=1}^k a_j^2 \right ),\ \text {and } e = \left ( \sum_{j=1}^k b_j^2 \right ).\)

\(\displaystyle \text {Note that } 0 \le c \le de.\)

\(\displaystyle \displaystyle \left ( \sum_{j=1}^{k+1} \{a_jb_j\}^2 \right ) = \left ( \sum_{j=1}^k \{a_jb_j\}^2 \right ) + a_{k+1}^2b_{k+1}^2 = c + a_{k+1}^2b_{k+1}^2 .\)

\(\displaystyle \displaystyle \left ( \sum_{j=1}^{k+1} a_j^2 \right ) \left ( \sum_{j=1}^{k+1} b_j^2 \right ) = \left \{ \left ( \sum_{j=1}^k a_j^2 \right ) + a_{k+1}^2 \right \}\left \{\left ( \sum_{j=1}^k b_j^2 \right ) + b_{k+1}^2 \right \} = \)

\(\displaystyle (d + a_{k+1}^2)(e + b_{k+1}^2) = de + a_{k+1}^2e + b_{k+1}^2d + a_{k+1}^2b_{k+1}^2 \implies\)

\(\displaystyle \displaystyle de + a_{k+1}^2b_{k+1}^2 = \left ( \sum_{j=1}^{k+1} a_j^2 \right ) \left ( \sum_{j=1}^{k+1} b_j^2 \right ) - (a_{k+1}^2e + b_{k+1}^2d).\)

\(\displaystyle \text {But } 0 \le (a_{k+1}^2e + b_{k+1}^2d)\ \because \text { every term is non-negative.}\)

\(\displaystyle \displaystyle \therefore de + a_{k+1}^2b_{k+1}^2 \le \left ( \sum_{j=1}^{k+1} a_j^2 \right ) \left ( \sum_{j=1}^{k+1} b_j^2 \right ).\)

\(\displaystyle \displaystyle \therefore c + a_{k+1}^2b_{k+1}^2 \le \left ( \sum_{j=1}^{k+1} a_j^2 \right ) \left ( \sum_{j=1}^{k+1} b_j^2 \right ) \ \because \ c \le de.\)

\(\displaystyle \displaystyle \text {But } \left ( \sum_{j=1}^{k+1} \{a_jb_j\}^2 \right ) = c + a_{k+1}^2b_{k+1}^2 .\)

\(\displaystyle \displaystyle \therefore \left ( \sum_{j=1}^{k+1} \{a_jb_j\}^2 \right ) \le \left ( \sum_{j=1}^{k+1} a_j^2 \right ) \left ( \sum_{j=1}^{k+1} b_j^2 \right ).\)

\(\displaystyle \displaystyle \text {THUS, by induction, for all } n \ge 1,\ \left ( \sum_{j=1}^n \{a_jb_j\}^2 \right ) \le \left ( \sum_{j=1}^n a_j^2 \right ) \left ( \sum_{j=1}^n b_j^2 \right ).\)

So nice
Thank you so much
 
Top